The brain as user interface [remotely guided rats]. - Moore, S.K (IEEE spectrum)
Neuroscientists have used a wireless receiver and electrodes implanted in a rat's brain to steer the rodent anywhere they want it to go. Suppose you want to guide a small robotic system through collapsed buildings to search for survivors. In pure robotics, this is a tough job. But remotely guided rats carrying wireless video cameras fit the bill nicely. The brain implant enables a trained rat to be instructed to turn right, turn left, or move forward according to keystrokes from a laptop as far as 500 meters away. Electrodes are implanted in three areas of the brain: one in the medial forebrain bundle (MFB), which is associated with feelings of pleasure, and one each in the left and right somatosensory cortex, part of the brain that handles the sense of touch. In particular, the electrodes are implanted in the parts of the cortex that sense the rat' s whiskers.